Risk factors for defaulted follow up for sharp injury among health care workers in Hospital Universiti Sains Malaysia - Kutubudin, Ahmed Farrasyah Mohd (2021)
Background: Sharp injury is a significant occupational health issue among health care workers (HCWs). It is one of the occupational-related hazards, especially in health care settings in clinics, hospitals, and labs. Despite the various effort, the prevalence of sharp injury remains high year by year. For Malaysia, it is being controlled by Quality Approach (QA) program with its specific indicator. However, it does not reflect on the prevalence. The number of under-reporting still very high, and the true number of infection from sharp injury remains uncertain because of the high number of defaulters for follow up. Objectives: To study the prevalence of defaulted follow up for sharp injury and its risk factors among health care workers in Hospital Universiti Sains Malaysia(HUSM). Methodology: The study applied a retrospective cohort study design using secondary data from Borang Insiden Kes Tercucuk Peralatan Tajam Database within a period of six years from January 2015. Data were collected using proforma and then transferred to Microsoft Excell. Analysis was done using SPSS version 26. There were 286 reported cases of sharp injury who fulfilled study criteria. All cases were selected for the study. Descriptive and logistic regression analyses were applied. Variables with p-value of less than 0.05 was judged to be statistically significant. Results:. The mean (standard deviation (SD)) age of those who had sharp injury was 29.4 (5.38) years old. Women and Malay ethnicity predominates the cases. Mostly the injury happened in the ward. Departments involving surgical procedure recorded the highest amount of injury. Job category pictured that most of the sharp injury cases were among house officers. Majority of the injuries were caused by needles and branula and mostly these devices were contaminated with blood and bodily fluids. From this study, we also noted that sharp injury mostly occurred when HCWs were handling the patients. All the reported cases must undergo treatment and follow up post exposure. However, from this study we found that there were two factors associated with defaulted follow up which were job category and type of devices used. HCWs who work as a doctor (Adj OR 2.37;95% CI: 1.40,4.03; p = 0.010) and those who used other sharp instruments such as Coupland, drip sets, and many others (Adj OR 4.55;95% CI: 1.59,13.02; p = 0.005) were at higher odds to default the follow up . Conclusion: Sharp injury is an issue that remained unresolved throughout the world generally and in Malaysia specifically. The risk to get the injury can occur to HCWs especially among those working as doctors and those involve with surgical procedure. Despite that, they are also more prone to default the treatment and follow up post sharp injury. A more intensive approach must be taken to handle and tackle this problem.